Construction and Development of Game-Specific Competitive Anxiety Questionnaire for Cricketers - R.Kalidasan2, P.Balaji1* and (Journal of Experimental Sciences, 2011)
The objective of the study was to assess the game-specific competitive anxiety level of the Tamilnadu state cricketers. One hundred and fifteen Cricketers from TNCA first division league cricket teams aged ranged between 16 and 26 years were respondent to questionnaire developed by the investigators and standardized sports competition anxiety questionnaire (SCAT) developed by Martens. The objectivity, reliability and validity of the questionnaire were established using appropriate tools. The three sports psychological experts were asked to subjectively rate the anxiety level of each cricketer in a 10 point scale, ranging from 0 to 10 point. The statistical analysis Pearson product moment correlation was used to find out the inter-relationship between expert rating and collected data. The result reveals that the constructed game-specific competitive anxiety questionnaire for Tamilnadu state cricketers had significant relationship with the expert rating and with SCAT questionnaire.